The Review on the Impacts of Climate Change on Biodiversity - Changkuoth Puok Diet (International Journal of Integrative Research, 2023)
Climate change is a significant global issue affecting biodiversity, genetics, species, and ecosystems. Therefore, this study was aimed to review the impact of climate change on biodiversity. Climate change affects terrestrial, marine, and freshwater ecosystems, causing ash conditions and affecting terrestrial ecosystems. To reduce climate change impacts, strategies must be developed through mitigation and adaptation measures. Mitigation measures involve reducing fossil fuel use and increasing carbon storage, while adaptation measures aim to adjust climate change's impact. By combining mitigation and adaptation measures, we can combat climate change's detrimental effects on biodiversity.